Inequity in uptake of maternal health care services in developing countries: a systematic review and meta-analysis - Gube, Addisu Alemayehu; Murányi, Edit; Vitrai, Jozsef; Lohner, Szimonetta (Frontiers in Public Health, 2024)
Background: Maternal health service uptake remains an important predictor of maternal outcomes including Maternal mortality. This systematic review and meta-analysis aimed to summarize the available evidence on the uptake of maternal health care services in developing countries and to assess the impact of place of residence, education status, and wealth index on the uptake of these services.Methods: We examined the databases MEDLINE, Web of Science, Global Index Medicus, and Scopus until June 14, 2022. Cross-sectional studies done between 2015 and 2022 were considered.Mothers of reproductive age and all states of health were included in the study. Independently, two authors determined the eligibility of studies, extracted data, evaluated the risk of bias, and ranked the evidence's degree of certainty. To combine the data, we performed a random-effects metaanalysis. The PROSPERO registration ID is CRD42022304094.We included 51 studies. Mothers living in urban areas were three times more likely to receive antenatal care (OR 2.95; 95% CI 2.23 to 3.89; 15 studies; 340,390 participants) than rural mothers. Compared with no education, those with primary education were twice as likely to utilize antenatal care (OR 2.36; 95% CI 1.80 to 3.09; 9 studies; 154,398 participants) and those with secondary and higher education were six and fourteen times more likely to utilize antenatal care, respectively. Mothers in the second wealth index were twice as likely as mothers in the lowest wealth index to utilize antenatal care (OR 1.62; 95% CI 1.36 to 1.91; 10 studies; 224,530 participants) and antenatal care utilization increased further among mothers in the higher wealth index. We observed similar relative inequalities in skilled delivery care and postnatal care utilization based on the pace of residence, education, and wealth index. Formatted: Font color: Red Conclusion: In developing countries, the problem of inequity in utilizing maternal health care services persists and needs considerable attention.